Perunding Sinar Teguh Sdn Bhd / Muhammad Fuad Mohd Azhari - Mohd Azhari, Muhammad Fuad (Faculty Of Civil Engineering, 2020)
Industrial Training is a compulsory requirement for students in certain programs at all level of higher education in Institutions of Higher Learning. It is also to satisfy the Engineering Technician Education Programme Accreditation Standard (ETAC) accreditation objective for Continual Quality Improvement (CQI) and to set a tool of benchmark for all diploma graduate holder. In this industrial training session, student got many new knowledge and experience that can only be achieved through the experience sharing by the industrial player and task that they already provided. It is very helpful in order for student to make sure that they are ready and competent enough to be in this challenge industry through up and down. Time and mental management are two of the crucial things that need to be managed in best possible way in order to avoid any possible mental health crisis and unnecessary work load. Networking and negotiating are two of the new things that can required through meeting and discussion with all parties that involve in this challenge industry is an important skill that need to be learned and mastered